The history of double tax conventions in Croatia - Hrvoje Arbutina; Nataša Žunić Kovačević (Financial Theory and Practice, 2014)

(untitled)
After a short introduction, the authors briefly describe the national experience in handling the problems of international double taxation through double tax conventions. This chapter is divided according to stages in the history of double tax conventions identified. The authors analyse the goals of tax treaty policies in differentiated stages with a survey of the economic implications. Special focus is placed on inter-country influences and the impact on and of international institutions and organisations through an examination of the influence of bilateral tax treaties on model tax conventions and vice versa. The fifth chapter presents concluding observations.